PERANAN PENDIDIKAN AGAMA KRISTEN DALAM MENGEDUKASI PESERTA DIDIK TENTANG BAHAYA PENYALAHGUNAAN NARKOBA - Roce Marsaulina; Dan Kia; Abraham Tefbanna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
We, the team that initiated this PKM activity, collaborated with BNN through GERAM as a driving force in the prevention and eradication of drug abuse in Indonesia. The purpose of this PKM is to educate students at SMPS Mitra in Kampung Cina – Tajurhalang – Bogor so that they know about the dangers of drug abuse, recognize the types of drugs, the symptoms of victims of drug abuse so that they do not get involved, but participate in its prevention. In realizing the activities of educating the public (students) about the dangers of drug abuse this time, it was held in the form of seminars for students. Drug abuse is an act that destroys the body which is the temple of God, because God's word explicitly says that our bodies are God's temples where God's Spirit dwells. This is where the role of PAK in the family, church, school and community is very much needed. So that students, parents and educators understand that it is better to prevent or not touch drugs at all than to treat them, which is the hope of the activities carried out.